Air‐Stable Ultra‐Flexible Organic Photonic System for Cardiovascular Monitoring. Issue 9 (3rd May 2022) - Yokota, Tomoyuki; Shirayama, Iwao; Kuwada, Kenji; Koizumi, Mari; Yukita, Wakako; Morii, Katsuyuki; Fukagawa, Hirohiko; Shimizu, Takahisa; Fukuda, Kenjiro; Someya, Takao
Abstract: Ultra‐flexible organic optical devices are increasingly attracting attention as devices for medical and healthcare applications because they can be directly attached to the skin and continuously monitor biological information in humans noninvasively. However, integrating different optical devices on the same ultra‐flexible substrate is difficult owing to the instability of the devices. In this study, the stability of ultra‐flexible organic light‐emitting diodes and photodiodes is successfully improved using an inverted structure that does not employ atmospherically unstable cathode materials. Furthermore, an ultra‐flexible organic pulse wave sensor is developed by integrating an organic light‐emitting diode and an organic photodiode on the same substrate. Abstract : Ultra‐flexible organic pulse wave sensor. The device consists of organic light‐emitting diodes and organic photodiodes on the same substrate. It functions as systolic blood pressure by combing the pulse wave sensor with a textile‐type ECG sensor.